1996
DOI: 10.1088/0953-8984/8/11/006
|View full text |Cite
|
Sign up to set email alerts
|

The electrodynamic response of single crystals of the quasi-two-dimensional organic metal between 50 and 100 GHz: observation of cyclotron resonance and quantum oscillations

Abstract: The electrodynamical response of single crystals of the quasi-two-dimensional organic metal has been studied in the frequency range 50 - 100 GHz in magnetic fields of up to 15 T, and at temperatures down to 1.5 K. The experiments were carried out using the cavity perturbation technique; the cavity was rectangular, allowing the high-frequency currents in the sample to be excited in two different geometries. A prominent feature attributed to cyclotron resonance was observed, corresponding to a cyclotron mass of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 16 publications
1
30
1
Order By: Relevance
“…of Reference [1], many of the earlier experiments were seriously flawed, and reliable experiments had to await the development of resonant cavity techniques [63,65,64]. Since such measurements became feasible, only two superconducting salts have yielded cyclotron resonance data.…”
Section: Renormalising Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…of Reference [1], many of the earlier experiments were seriously flawed, and reliable experiments had to await the development of resonant cavity techniques [63,65,64]. Since such measurements became feasible, only two superconducting salts have yielded cyclotron resonance data.…”
Section: Renormalising Interactionsmentioning
confidence: 99%
“…Since such measurements became feasible, only two superconducting salts have yielded cyclotron resonance data. In α-(BEDT-TTF) 2 NH 4 Hg(SCN) 4 , which is believed to have a simple Fermi surface consisting of a pair of sheets and a closed pocket, a cyclotron resonance corresponding to a mass of 1.9m e was measured [64,65]; this may be compared with an effective mass from magnetic quantum oscillations of 2.5m e [67]. β ′′ -(BEDT-TTF) 2 SF 5 CH 2 CF 2 SO 3 , again with a Fermi surface believed to consist of a single pocket and a pair of sheets (but see Reference [66]), exhibited a cyclotron resonance corresponding to a mass of 2.2m e [31] (see Figure 9) the effective mass from Shubnikovde Haas oscillations is 1.9m e [68].…”
Section: Renormalising Interactionsmentioning
confidence: 99%
“…In particular, attention has focused on the well characterized -(ET) NH Hg(SCN) organic conductor which, in contrast to its -phase counterparts, is known to possess a somewhat simpler FS and remains metallic down to 1 K, at which point it becomes superconducting [3]. However, a wide range of conflicting values for the effective mass, deduced from CR (m !0 ), have been reported for this material [11,12,17]. A recent study by Hill [18] has shown how many of these results may be reconciled; it is predicted that a novel CR behavior results from the unique FS topologies common to these highly anisotropic conductors, and that the resonance condition is highly sensitive the exact geometry in which the experiment is carried out.…”
Section: Cyclotron Resonancementioning
confidence: 90%
“…Another advantage of this technique is that, by carefully positioning the sample within the cavity, one can excite AC currents in any desired direction within the sample [9]. The so-called 'cavity perturbation' technique has been used by several groups to study molecular conductors [9,10], however, there are relatively few reports involving high magnetic fields [11][12][13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation